2012
DOI: 10.7771/1541-5015.1312
|View full text |Cite
|
Sign up to set email alerts
|

“I Know This is Supposed to be More Like the Real World, But . . .”: Student Perceptions of a PBL Implementation in an Undergraduate Materials Science Course

Abstract: This qualitative case study examines the initial implementation of a problem-based version of an undergraduate course in materials science for the purpose of identifying areas of improvement to the curriculum prior to a planned second implementation. The course was designed around problems that students work in small teams to solve under the guidance of facilitators, with early sequence problems designed to foster the problem-solving skills required to succeed in the course. This report describes students' imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 26 publications
0
41
1
1
Order By: Relevance
“…Notably, our findings suggest that this negotiation is one of the most difficult tasks for instructors and advisors to implement well in PBL courses: balancing students' needs for empowerment and self-direction with their need to be provided with the support necessary to be successful. Some groups of students in our study wanted more guidance (i.e., more "hands-on"), whereas others liked the "hands-off" approach because they felt empowered by their freedom, echoing and extending the student perceptions identified by Henry et al (2012) in exploring PBL in a materials science course. The amount of help each group needed varied, but advisors need to understand what students prefer or expect, and then work with them to create an environment in which the students feel supported, even if that environment does not match the students' or advisor's preferences.…”
Section: Role Of the Instructors And Advisorsmentioning
confidence: 70%
See 2 more Smart Citations
“…Notably, our findings suggest that this negotiation is one of the most difficult tasks for instructors and advisors to implement well in PBL courses: balancing students' needs for empowerment and self-direction with their need to be provided with the support necessary to be successful. Some groups of students in our study wanted more guidance (i.e., more "hands-on"), whereas others liked the "hands-off" approach because they felt empowered by their freedom, echoing and extending the student perceptions identified by Henry et al (2012) in exploring PBL in a materials science course. The amount of help each group needed varied, but advisors need to understand what students prefer or expect, and then work with them to create an environment in which the students feel supported, even if that environment does not match the students' or advisor's preferences.…”
Section: Role Of the Instructors And Advisorsmentioning
confidence: 70%
“…Their study also documented that stress-related factors were dominant predictors of engagement and persistence, and that autonomy (aligned with empowerment in the present study) was a strong support system; the link here between empowerment and particular course elements such as project selection and control extend the quantitative results evidenced in that work. Similarly, several studies have highlighted the mentor role in student engagement (e.g., Ge, Huang, & Dong, 2010;Henry et al, 2012) and the findings provide a direct link between specific facilitator behaviors and robust motivation constructs.…”
Section: Empowermentmentioning
confidence: 75%
See 1 more Smart Citation
“…In particular, the year-long experience enhanced students' multidisciplinary problem-solving skills and their ability to work effectively in teams. However, Henry, Tawfik, Jonassen, Winholtz, and Khanna (2012) found that PBL presented significant challenges to undergraduate engineering students; in particular, the students missed traditional faculty lectures and struggled to work successfully in groups. In fact, most of the studies cited above echo the findings of Henry et al that students struggle with the unfamiliarity of the PBL environment, which poses challenges for implementation.…”
Section: Pbl In Higher Educationmentioning
confidence: 99%
“…The students in this study expressed an awareness that not all of the feedback from the TA was relevant to their work. In other PBL studies, students have expressed dissatisfaction with vague feedback from their instructors (Henry, Tawfik, Jonassen, Winholtz, & Khanna, 2012). Nelson and Schuun (2009) also suggest that feedback should avoid praise because it can be misguiding.…”
Section: Effective Feedback: Students' Perspectives Vs Researchmentioning
confidence: 99%